2016
DOI: 10.1007/s12402-016-0207-4
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service teachers’ perceptions of sluggish cognitive tempo

Abstract: Sluggish cognitive tempo (SCT) is characterized by a passive form of inattention that may not overtly disrupt classroom goals. Due to the nature of these symptoms, children with SCT may be "falling through the cracks" in schools. The current study examined pre-service teachers' perceptions of SCT in the classroom. Undergraduate education majors (n = 161) read vignettes describing fictitious fourth-grade boys presenting with symptoms of SCT, attention-deficit/hyperactivity disorder (ADHD), or a non-ADHD-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Examined unidimensionally, SCT has been found to be associated with greater social withdrawal, peer ignoring, lower rates of social participation and leadership, and a higher likelihood to miss subtle social cues (Becker et al, 2017; Marshall, Evans, Eiraldi, Becker, & Power, 2014; Mikami, Huang-Pollock, Pfiffner, McBurnett, & Hangai, 2007). There is also preliminary evidence that teachers may be concerned with SCT behaviors, as Meisinger and Lefler (2017) found that preservice teachers rated similar levels of concern for students described as having SCT, ADHD, or social anxiety, and also rated SCT behaviors as worthy of a referral for services. As a multidimensional construct, Fenollar Cortés and colleagues (2017) reported a two-factor structure of SCT in a sample of children and adolescents with a diagnosis of ADHD that included an inconsistent alertness factor (e.g., daydreams, absentminded) and a slowness factor (e.g., seems drowsy, slow moving).…”
Section: Sct and Children’s Social Functioningmentioning
confidence: 99%
“…Examined unidimensionally, SCT has been found to be associated with greater social withdrawal, peer ignoring, lower rates of social participation and leadership, and a higher likelihood to miss subtle social cues (Becker et al, 2017; Marshall, Evans, Eiraldi, Becker, & Power, 2014; Mikami, Huang-Pollock, Pfiffner, McBurnett, & Hangai, 2007). There is also preliminary evidence that teachers may be concerned with SCT behaviors, as Meisinger and Lefler (2017) found that preservice teachers rated similar levels of concern for students described as having SCT, ADHD, or social anxiety, and also rated SCT behaviors as worthy of a referral for services. As a multidimensional construct, Fenollar Cortés and colleagues (2017) reported a two-factor structure of SCT in a sample of children and adolescents with a diagnosis of ADHD that included an inconsistent alertness factor (e.g., daydreams, absentminded) and a slowness factor (e.g., seems drowsy, slow moving).…”
Section: Sct and Children’s Social Functioningmentioning
confidence: 99%
“…Its articles focus on aspects related to non-pharmacological interventions (Kysow et al 2017;Philipsen et al 2017) and pharmacological treatment (Tanaka et al 2017). Moreover, the genetic association between ADHD and Parkinson's disease (Geissler et al 2017) as well as pre-service teachers' perceptions of sluggish cognitive tempo (Meisinger and Lefler 2017) are elucidated.…”
mentioning
confidence: 99%